The use of epoetin alfa biosimilar in the anemia management in hemodialysis patients - Dudar, I. O.; Krasjuk, E. K.; Honchar, Y. I.; Loboda, O. M.; Shifris, I. M.; Krot, V. F.; Savchuk, V. M. (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. The present study aimed to evaluate the efficacy and safety of EMAVAIL (epoetin alfa) in the correction of anemia in hemodialysis patients. Methods. A total of 36 patients undergoing regular hemodialysis were enrolled in this prospective study. Among the patients were 19 (53%) men and 17 (47%) women with severe anemia (hemoglobin (Hb) level ≤ 90 g/L). The mean patients’ age was 48.41±1.82 years, an average dialysis vintage consisted of 42.38±10.41 months. All the patients had thrice-weekly hemodialysis sessions, with a mean duration of 12.6 ± 0.51 hours per week and Kt/V 1.27 ± 0.08. All the patients were treated with biosimilar of epoetin alfa EMAVAIL intravenously three times a week in adjustable doses. The follow-up period was 56 days. Results. At the study entry, the mean Hb level in hemodialysis patients was 81.7±0,93 g/L. In 56 days of anemia treatment, the concentration of Hb increased to 109.17±1.75 g/L. Eventually, 32 (89%) patients achieved the target Hb level (110 g/L); 6 (17%) patients had adverse events (mild hypertension). There were no serious adverse events. Conclusions. EMAVAIL is an effective and safe epoetin alfa biosimilar for anemia management in hemodialysis patients.